The Сustomer Experience Management as a Strategy For Business Development - Sytnik Natalia I. (Research Centre of Industrial Problems of Development of NAS of Ukraine, 2021)
Against the background of rising consumer expectations and increased competition, competence in customer experience management becomes a factor in the survival of modern companies. To achieve sustainable customer commitment, companies have to master the skills of effective interaction with customers and learn how to manage customer experience. This makes a study, concerned with developing a strategy for managing customer experience, relevant. The purpose of the article is to study the strategic aspects of customer experience management, in particular in identifying the sequence of stages of strategy development, defining their essence, instrumentarium, and conditions for implementation in the company’s business processes. The development of a customer experience management strategy is aimed at improving the efficiency of the customer experience value chain, which begins with communications at contact points and results in additional income from the growth of the company’s brand capital. The analytical, organizational, managerial, and control-evaluation measures are distinguished in the structure of the client experience management process. The author suggests a general scheme of development of customer experience management strategy in the form of step-by-step cyclical process consisting of eight consecutive stages: formation of service vision; structuring contact points; defining the needs to improve customer experience; development of an action plan; defining budget and resources; distribution of roles and areas of responsibility of subdivisions; creation of a new brand experience of customers and evaluation of results of its implementation. The tools for collecting and analyzing customer experience and customer service are systematized, specific management measures for their improvement are proposed.